Bridging the Acute-to-Outpatient Care Gap in Mental Health: Developing and Implementing a Mental Health Transition Process. Issue 3 (4th July 2022) - Kantaria, Tina; Talag, Germiniano; Fan, Jia; Navarro, Filda; Sonza, Patrick; Fears, Scott; Yang, Calvin; Balsam, Jeffrey; Birman, Sharon; Lam, Mona; Guze, Barry; Raja, Pushpa
Abstract : Background: A national Department of Veterans Affairs (VA) mental health (MH) quality metric tracks engagement in outpatient MH care after discharge from residential and inpatient settings, with recommendations for 2 or more visits 30 days postdischarge. Local Problem: A gap in transitioning patients from residential to outpatient MH care was identified at this site. Methods: A transition management process was developed and piloted, including a new MH Discharge Consult and an RN Transition Care Managers team. Interventions: Transition Care Managers triaged Discharge Consults, communicated with schedulers and patients pre- and postdischarge, and tracked MH engagement for 30 days postdischarge. Process, outcome, and balancing measures were developed and iteratively adjusted using Plan-Do-Study-Act (PDSA) cycles. Results: Over 55 weeks, 443 Discharge Consults were placed. There was an average 89% success rate in connecting patients with 2 or more MH visits versus 53% preintervention. Conclusions: This pilot showed promising results in improving postdischarge MH engagement with the use of PDSA cycles to collect data and refine processes.